Experiences on time for work and leisure - Hercílio de Brito Filho, Francisco; Martins, José Clerton de Oliveira (Revista de Psicologia, 2014)
This article results from an exploratory study about work and leisure. Its objectives were to check how workers with higher education assess the quantitative distribution of their time and also to analyze how they assess the quality of the experiences they come across during both their work and free time. A questionnaire was used with 62 postgraduate-level students who are active workers. The data was analyzed both quantitatively and qualitatively. The main results indicate negative assessment on time distribution for work and leisure and on the quality of the experiences lived in each of these moments although the experiences which happened during leisure time were more valued by the subjects. The conclusion was that it is important that leisure, as part of a whole human experience, be redefined in the workers’ lives, and that they relearn how to live their lives in a slower, lighter, and more meaningful way.